Seals as a Reflection of the Self-Confidence, Self-Image and Identity of the Teutonic Order - Katharina Kemmer (Religions, 2024)
This article deals with the question of the extent to which the Teutonic Order, as a clerical order of knights founded during the Third Crusade, succeeded in expressing its self-confidence and identity by means of its seal. The “geographical” area of investigation extends to the bailiwicks of Franconia, Alsace–Burgundy, Lorraine, Austria, An der Etsch and in the mountains (South Tyrol) as well as the so-called Deutschmeistertum, whereby the terms mentioned do not necessarily correspond to the present-day areas of that designation. The time frame is within the Middle Ages. Due to the large number of surviving seals of the Teutonic Order, however, only a small insight from a larger study can be provided here. Selected seals of the Order’s various internal leadership strata are therefore presented, compared and examined to determine whether and to what extent they express a form of self-confidence and identity.